Performance Analysis of Helical Gear - Nakkeeran, S. (International Journal of Psychosocial Rehabilitation, 2019)
Helical gears are widely used in industry where the power transmission is required at heavy loads with smoother and noiseless operation. Helical gear are generally used to transmit power or torque for transmission at very high speed when compared to other kind of gear transmissions this application are explain the design the helical gear with defined specification. It’s have an involving modern design, specific character, specific materials, with consideration of analysis of force, and its mechanical properties. In this project we design the helical by using solid works 2016 premium and perform the analysis by using solid works simulation by using different materials and different loads applied on it